(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article analyzed the areas of development of human capital in our country, the importance of investments in human capital in the effective management of human resources, the scientific and theoretical views of foreign and domestic scientists on this matter, experiments. As a result of the analysis, scientifically based proposals and recommendations for the development of human capital were developed